2003
DOI: 10.1023/a:1024406223619
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Estrogen Receptor-β in Normal Mammary and Tumor Tissues: is it Protective in Breast Carcinogenesis?

Abstract: Using messenger RNA (mRNA) in situ hybridization, we investigated estrogen receptor-beta (ERbeta) mRNA levels in normal mammary, benign breast tumor (BBT), breast cancer (BC), and metastatic lymph node tissues to verify the role of ERbeta in BC development and progression. ERbeta expression was significantly decreased in BC and metastatic lymph node tissues compared with normal mammary and BBT tissues (p < 0.01). The intensity and extent of ERbeta mRNA signals were also significantly lower in BC and metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 16 publications
5
42
0
2
Order By: Relevance
“…Instead, decreased expression of ERb was observed in cells with forced expression of ARTN. Several reports have described loss of ERb during mammary tumorigenesis, supporting the potential role of ERb as a tumor suppressor (Park et al, 2003;Shaaban et al, 2003;Bardin et al, 2004;Rody et al, 2005). ERb has been reported to modulate ERa activity and cellular response to estrogen (Hall and McDonnel, 1999;Pettersson et al, 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Instead, decreased expression of ERb was observed in cells with forced expression of ARTN. Several reports have described loss of ERb during mammary tumorigenesis, supporting the potential role of ERb as a tumor suppressor (Park et al, 2003;Shaaban et al, 2003;Bardin et al, 2004;Rody et al, 2005). ERb has been reported to modulate ERa activity and cellular response to estrogen (Hall and McDonnel, 1999;Pettersson et al, 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Estrogen receptor b (ER b) expression was observed to be significantly decreased in breast cancer and metastatic lymph node tissues compared with normal mammary and benign breast tumors (Park et al, 2003). An inverse relationship was found between ER b mRNA level and both histologic grade and progesterone receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…ERb expression was decreased in BC and metastatic lymph node tissues as compared with normal mammary and benign breast tumor (BBT) tissues. The intensity and extent of ERb expression were significantly higher in normal and BBT tissues than in BC or metastatic lymph node tissues (Park et al 2003).…”
Section: Analysis Of Era and Erb Expression In Estrogen-sensitive Canmentioning
confidence: 86%
“…Similar findings were obtained at the mRNA level by the RT-PCR method by Iwao et al (2000), who also showed that ERa mRNA is increased and ERb mRNA decreased during breast carcinogenesis. Recently, Park et al (2003) compared ERb mRNA levels in various breast tissues, using mRNA in situ hybridization. ERb expression was decreased in BC and metastatic lymph node tissues as compared with normal mammary and benign breast tumor (BBT) tissues.…”
Section: Analysis Of Era and Erb Expression In Estrogen-sensitive Canmentioning
confidence: 99%